12 Literature Matters Today. - Miller, J. Hillis (Substance: A Review of Theory & Literary Criticism, 2013)
In this article, the author reflects on the question of whether literature matters in today's world with human beings across the world. He discusses two assumptions related to why literature matters in Victorian and in European culture generally. He mentions that literature in the sense of printed poems, plays, and novels are mattering less and less to many people, including highly educated ones.